If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2y + 6) + 2y = 12 Reorder the terms: 2(6 + 2y) + 2y = 12 (6 * 2 + 2y * 2) + 2y = 12 (12 + 4y) + 2y = 12 Combine like terms: 4y + 2y = 6y 12 + 6y = 12 Add '-12' to each side of the equation. 12 + -12 + 6y = 12 + -12 Combine like terms: 12 + -12 = 0 0 + 6y = 12 + -12 6y = 12 + -12 Combine like terms: 12 + -12 = 0 6y = 0 Solving 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '6'. y = 0 Simplifying y = 0
| 6h+4-3+6h=11 | | (2y-64)+(2y)=180 | | (7y^3-3y^2+4y)+(8y^4+3y^2)= | | 2x+5=9+3x | | (1-2x)=-2-(3+x) | | 3(r-4)=12 | | 0.7x+16+4w=27.28 | | 50=-6x+4x-3-8 | | 186=-6(5-4x)+3x | | 5y-8-3y+12= | | 8x+78=2x+3 | | x^3-a=0 | | C*4=20 | | j-(-18)=94 | | 180-70= | | Q+6=36 | | 15m=1.25 | | lnx^4-7lnx=1 | | (17n^4+2n^3)-(10n^4+n^3)= | | 22.41*2-5.09= | | 2x=10+2x | | logx+log(x+2)=log(3x) | | 10n+7-3n+5= | | (n+6)=(3n-10) | | -480=-8(4-7r) | | (-5)9x-15=-465 | | 5-3x+8x=6-2x+3x | | -x^2-6x-10=-1 | | f(x)=2tanx | | 4n-2-7n=20 | | -4[x+2(5xy-x)]= | | X(2)+4x-2=0 |